2016
DOI: 10.1136/annrheumdis-2016-209511
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity states of the DAPSA, a psoriatic arthritis specific instrument, are valid against functional status and structural progression

Abstract: IMPACT 2: NCT02152254; GO-REVEAL: NCT00265096.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 14 publications
1
53
0
1
Order By: Relevance
“…There are a variety of disease assessments for PsA. DAPSA, cDAPSA, and MDA are composite indices and have been validated and promoted for use in estimating disease activity for PsA by the international task force . In the multivariable regression analysis of the present study, two disease activity indices (cDAPSA and DAPSA) and HAQ were significantly associated with HU after adjusting for age.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…There are a variety of disease assessments for PsA. DAPSA, cDAPSA, and MDA are composite indices and have been validated and promoted for use in estimating disease activity for PsA by the international task force . In the multivariable regression analysis of the present study, two disease activity indices (cDAPSA and DAPSA) and HAQ were significantly associated with HU after adjusting for age.…”
Section: Discussionmentioning
confidence: 59%
“…The target of treatment of PsA in the 2017 update of recommendations by an international task force is clinical remission or minimal disease activity . Patients with clinical remission had the best function and the fewest radiographic outcomes . The validated measures of PsA including Disease Activity Index for Psoriatic Arthritis (DAPSA), the clinical DAPSA (cDAPSA), and the minimal disease activity (MDA) have been suggested to measure the target of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators in other studies did assess the burden of disease in patients fulfilling only 1 of the targets compared with those not fulfilling that target. It was shown in those studies that patients achieving the target had better scores for patient-reported outcomes compared with patients in whom the target was not achieved (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental question that remains is how to identify the most appropriate instruments to monitor disease activity in patients with PsA who may have multiple manifestations in clinical practice. In this regard, treatment‐to‐target and American College of Rheumatology recommendations for PsA support the use of the Disease Activity Index for Psoriatic Arthritis (DAPSA) as a valid instrument to monitor the achievement of treatment targets among other treatment targets . A potential, inherent limitation associated with the DAPSA relates to its focus on articular features.…”
Section: Introductionmentioning
confidence: 99%